IMPLEMENTASI AI GENERATIF DALAM MENGURANGI BEBAN ADMINISTRASI GURU: STUDI KASUS KUALITATIF DI SEKOLAH DASAR ISLAM DENGAN PENDEKATAN TRANSFORMASI DIGITAL - Muhammad Zulfikar; Sri Handayani; Eva Dianawati Wasliman (STKIP Subang, 2026)
This study explores the implementation of generative artificial intelligence (AI) in reducing teachers' administrative burden at SD Islam Hasyim Asy'ari Cisarua through a qualitative case study. High administrative burden often hinders teachers' focus on learning activities. The method involves in-depth interviews with four key informants: Vice Principal for Curriculum, Treasurer, and two Program Coordinators. Data were analyzed using thematic-descriptive analysis to identify time efficiency, output quality, and challenges. Results show that AI tools such as ChatGPT and Google Gemini reduced lesson plan preparation time by 40-50% (from 2-3 hours to 45-60 minutes), evaluation questions, and report narratives. Output quality improved in structure, consistency, and formal language, but requires teacher curation for Islamic context. Challenges include digital literacy gaps, limited infrastructure, and technology dependency. Research novelty lies in AI integration with Islamic values, impacting teacher productivity and digital transformation. Recommendations: Strengthen TAM-based training, Kemdikbud infrastructure policies, and further mixed methods research for scalability.